Incidência e mortalidade por câncer no estado de Mato Grosso, 2000 a 2016 - Modesto, Viviane Cardozo (2022)
Introduction: Cancer is one of the most common causes of death and its incidence is increasing worldwide and stands out as one of the main public health problems. Incidence and mortality rates are considered epidemiological surveillance control measures, through which it is possible to analyze the occurrence, distribution and evolution of diseases, in the same way to know information about the profile of different types of cancer in a given territory. and characterize possible scenario changes over time. Objective: To analyze the temporal trend of the mortality rate and cancer incidence in the state of Mato Grosso, from 2000 to 2016. Methods: This is an ecological study, of the time series type, based on mortality and cancer incidence according to the International Classification of Diseases - ICD 10 (C00 to C97) obtained from the Mortality Information System (SIM) from 2000 to 2016, and Population-Based Cancer Registry (RCBP) from 2001 to 2016. cancer mortality rates per year for the state of Mato Grosso and by health regions. The time trend of the standardized cancer mortality rate was analyzed by linear regression, and the annual percentage change (APC) was calculated. Thematic maps of standardized rates were constructed. A descriptive analysis of new cases was performed and the standardized incidence rate was calculated according to gender and health macro-regions. For trend analysis, Joinpoint regression was used. The Annual Percent Change (APC) and Average Annual Percent Change (AAPC) were calculated. Results: In the period from 2000 to 2015, there were 28,520 deaths from cancer, which represented 12.8% of the total number of deaths in the State of Mato Grosso, 58.0% of which were male, 59.1% between 30 and 69 years of age and 36 .5% aged 70 or over. The five types of cancer that killed the most were lung, prostate, stomach, breast and liver. The regions Baixada Cuiabana (37.3%), Sul Matogrossense (17.1%), Teles Pires (8.6%), Oeste Matogrossense (6.7%) and Médio Norte Matogrossense (5.8%) accounted for 75 .5% of total cancer deaths and are the most populous in the state. The mortality rate standardized by cancer in Mato Grosso went from 74.3 in 2000 to 82.0 in 2015, for every 100 thousand inhabitants. The trend towards an increase in the mortality rate was observed in the State of Mato Grosso (APC=0.81%), and in four health regions, Garças Araguaia (APC=2.27%), Sul Matogrossense (APC=1.12 %), Teles Pires (APC=1.93%) and Vale dos Arinos (APC=2.61%). The state reported 74,756 new cases of cancer in the period from 2001 to 2016 and the most frequent types in males were prostate, lung, stomach, colorectal and esophagus, while in females were breast, cervix, colorectal, lung and stomach. For men, in the period from 2001 to 2016, prostate cancer showed an increase trend of 7.1% in the period in the East macro-region, 5.9% in the West, 4.7% in the South, 4.5% in the North Center and in the state of 1.7%. For lung cancer there was a reduction of -3.5% in the East macro-region. For colorectal cancer, there was an increase of 4.3% in the incidence rate in the North macroregion. For stomach cancer, a reduction of -4.5% was observed in the North macro-region, - 2.7% in the Center Northwest and -3.3% in the state. For esophageal cancer, there was a reduction only for the Central Northwest macro-region (-4.5%). In women, breast cancer had a reduction of -3.0% in the period from 2001 to 2009 in the Central-North macro-region and an increase of 6.8% in the period from 2009 to 2016 for the state. For cervical cancer, the trend was decreasing in the state and in all macro-regions. For lung cancer, the North Central macroregion showed an increasing trend (2.6%) and the South had a break in the series, with a decreasing trend in the period from 2001 to 2007 (-8.4%) and increasing in the period from 2007 to 2016 (7.9%), and the same was observed for the state with a decreasing trend (-2.9%) from 2001 to 2008 and increasing (4.8%) from 2008 to 2016. For colorectal cancer, the trend was stable for all macro-regions and the state. For stomach cancer, there was a reduction in the Central Northwest macro-region (-5.9%) and in the state (-2.5%). Conclusion: The importance of recognizing the territory of the state of Mato Grosso is highlighted, so that there is a strengthening of prevention and health promotion actions, in order to reduce morbidity and mortality from cancer and provide better quality, signaling the need to strengthen actions of cancer control.